IMPLEMENTATION OF MOTIVATION IN AN EFFORT TO INCREASE THE WORK PRODUCTIVITY OF HOSPITAL EMPLOYEES - Anry Sutrisno; Andhika Lungguh Perceka; Muhammad Sidik Nurjaman (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Work motivation is defined as a willingness to exercise high levels of effort to achieve organizational goals which are conditioned by the ability of the effort to meet certain needs. So the company as the authority holder also makes policies that must be able to understand the motives of its employees in working. Because, employee work motivation and productivity have been proven to be interrelated. So in this case, if companies can understand work motivation which includes internal and external dimensions, efforts to increase employee work productivity can be optimized and improved. Strategies for improving hospital employee performance can be carried out in various ways, starting from providing training and skills development, increasing motivation and work morale, to implementing an appropriate reward and punishment system. Apart from that, it is also important to pay attention to factors that influence employee performance, such as a conducive work environment, adequate management support, and effective work systems. In improving employee performance, hospital or health institution management needs to improve a positive organizational culture, provide a reward system and adequate work facilities, as well as provide mentoring or support to employees in carrying out their duties and responsibilities. Evaluation of the factors that influence employee performance needs to continue to be carried out to improve the performance and effectiveness of the institution as a whole.